Bactericidal Effects of Extract Basil Leaves in In-vitro Study of Pseudomonas aeruginosa - Deny Febriwijaya Romadhani; Achmad Hilman Fahmy; Ilham Putera Alam; Hotimah Masdan Salim (Biomolecular and Health Science Journal, 2020)
Introduction: Pseudomonas aeruginosa is the most common bacterial cause of nosocomial infections. Bacteria become resistant to antibiotics by various mechanisms, including producing enzymes that can damage antibiotics, change intracellular targets from antibiotics, and efflux pumps. Basil (Ocimum sanctum L.) is a traditional plant that is usually used as ingredients that contain antibacterial compounds including flavonoids, tannins, alkaloids, and eugenol. The aim was to determine the effectiveness of extract basil leaves for inhibiting and killing the growth of Pseudomonas aeruginosa.Methods: We administrated extract basil leaves with a concentration of 100%, 50%, and 25% in the plate contained bacterium Pseudomonas aeruginosa. The result showed that there was no inhibition of bacterial growth in broth dilution for 8 hours and 24 hours. We continued to culture bacteria for 24 hours.Results: The analysis showed extract basil leaves has bactericidal effects in 8 hours and 24 hours incubation significantly (p < 0.05). However, in 24 hours more effective as a bactericidal in 100% of concentration significantly (p < 0.05).Conclusion: From this result, eugenol (a phenol derivative found in the ethanol extract of basil leaves) has the effect of damaging cell membranes. Phenol bonding with bacterial cell walls can disrupt the permeability of transport cell membranes, thus the bacteria will be disrupted and die.